Black carbon aggregates: A database for optical properties. (January 2019) - Liu, Chao; Xu, Xiaofeng; Yin, Yan; Schnaiter, Martin; Yung, Yuk L.
Highlights: A comprehensive optical property database for black carbon (BC) aggregates is developed and evaluated. The implementation is used to calculate BC optical properties accurately and efficiently based on pre-calculated database. Examples to retrieve BC refractive index and calculate radiative properties are performed to show the importance of accurate optical property simulations. Abstract: Black carbon (BC) aerosol plays an important role in the atmosphere as an absorber of solar radiation and contributes significantly to global warming. The optical properties of BC are fundamental for both direct radiative effect studies and remote sensing of BC properties. However, due to the complex aggregation structures of BC particles, accurate simulations of their optical properties are limited and computationally expensive, while equivalent spherical models or approximate methods could easily introduce relative errors up to 30%. This study generates a comprehensive database to calculate aggregate optical properties efficiently and accurately. The database covers a wide range of BC properties including aggregation structure, refractive index, and particle size (both monomer size and number of monomers). An accurate numerical model, i.e. the multiple-sphere T-matrix method, is used to calculate the single-scattering properties of BC clusters in the form of fractal aggregates. By interpolation, the database can be used to give the scattering properties of aggregates with monomer number from 1 up to 3000, monomer size parameter from 0.05 to 0.5, real part of refractive index from 1.2 to 2.0, and imaginary part from 0.2 to 1.0. The relative errors caused by the interpolation are much less than 1% for the single scattering properties. The pre-calculated database and the implementation used to calculate the required aggregate optical properties are publicly available for users interested in remote sensing of BC aerosols and performing radiative effect calculations.